Wiadomości Dnia . 21 March 1981 - MKZ Wielkopolska, [ed. Biuro Prasowe MKZ-Wielkopolska] (MKZ NSZZ "Solidarność" Wielkopolska, 1981)
Creation and circulation: For organizational use; In February-April and August-December daily published without numeration, with dates. Numeration in issues no. 43(23.04.1981)- 122(19.08.1981)